2020
DOI: 10.1002/pa.2323
|View full text |Cite
|
Sign up to set email alerts
|

Does climatic risk induce labour migration? Evidence from Semi‐Arid Tropics region of India

Abstract: The paper aims to focus on climatic risk as a potential determinant of temporary labour migration in Semi-Arid Tropics (SAT) village in India for the year 2013-2014. Specifically, we address the question of how households use temporary labour migration as a coping mechanism to minimise the risk posed by climate variables such as drought, floods, cyclone etc. In doing so, the paper uses a binary choice model (logistic regression) to examine the potential socioeconomic and demographic factors along with climatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…Again both the studies did not find any statistical association between flood (“excess precipitation”) and migration. A similar finding also has come up from another study [ 29 ] which with the exploration of ICRISAT cross-sectional data of 2013–14 found that climatic risks (which was reported to be heavily related to drought) brings an increase in the probability of migration in semi-arid parts of India. Real and futuristic migration intentions data may produce somewhat contradictory associations with drought as one study [ 54 ] employing perceived increased severity of drought and future migration intentions, has reported a negative association between the two.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Again both the studies did not find any statistical association between flood (“excess precipitation”) and migration. A similar finding also has come up from another study [ 29 ] which with the exploration of ICRISAT cross-sectional data of 2013–14 found that climatic risks (which was reported to be heavily related to drought) brings an increase in the probability of migration in semi-arid parts of India. Real and futuristic migration intentions data may produce somewhat contradictory associations with drought as one study [ 54 ] employing perceived increased severity of drought and future migration intentions, has reported a negative association between the two.…”
Section: Discussionsupporting
confidence: 80%
“…The association between drought and human migration has been studied in many regions around the world including Brazil [15], Canada [16,17], China [18], Ethiopia [19,20], Kenya [21], Mali [22,23], Nepal [24], Northern Latin America and the Caribbean [25], Syria [26], United States of America [27] etc. In India, a few studies have found a positive association between drought and migration by analysing Census of India and International Crops Research Institute for the Semi-Arid Tropics (ICRISAT) datasets [28][29][30]. This association between drought and migration is also evidenced in a few field based studies spread across different parts of India like Karnataka [31], Odisha [32][33][34], Tamil Nadu [35], West Bengal [36,37], Hindu Kush-Himalayas [38] etc.…”
Section: Introductionmentioning
confidence: 93%
“…Furthermore, industrial development also depends on the agriculture sector because 60 per cent of industrial establishments in Pakistan are agro-based. This sector also provides raw materials for domestic industries like rugs, carpets, sugar, leather, footwear and food products (Pradhan et al, 2022). Agriculture laborers play a crucial role in providing food, reducing hunger and national development, but unfortunately, the socioeconomic condition of these laborers is deplorable.…”
Section: Introductionmentioning
confidence: 99%